Penerapan Prototyping dalam Perancangan Sistem Informasi Surat Masuk dan Surat Keluar (Studi Kasus Digitalisasi Administrasi) - Nofa Rizki Ramadhina; Mutiara Handayani Ujianti (Infotek: Jurnal Informatika dan Teknologi, 2026)
The rapid growth of information technology encourages educational institutions to improve administrative efficiency, particularly in managing incoming and outgoing letters as part of formal communication. Manual procedures that rely on agenda books and physical document storage often result in delayed dispositions, difficulty retrieving documents, and a higher risk of misplaced or lost records. This study aims to design a web-based correspondence information system as a more structured, accessible, and efficient solution to these issues. A qualitative descriptive approach was applied, using observation, interviews, and literature review, followed by system requirements analysis aligned with operational needs. The design process employed a prototyping method and was documented using UML-based modeling to represent both structure and workflow. The results of this study produce a system design that supports digital recording, electronic archiving, online disposition, and automated notifications. The primary contribution of this research is the development of a relevant and applicable system model that aligns with modern administrative digitalization, offering potential improvements in workflow efficiency, information distribution speed, data accuracy, and secure traceability of administrative records.